2004
DOI: 10.1177/030089160409000126
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Pulmonary Adenocarcinoma in a Patient with Job's Syndrome, A Rare Immunodeficiency Condition

Abstract: The hyperimmunoglobulin E (HIE) (Job's) syndrome often has it onset in childhood and is characterized by markedly elevated serum IgE levels, chronic dermatitis and recurrent pyogenic infections. Lymphoid malignancies have most commonly been associated with this syndrome while the first case in the literature of carcinoma associated with HIE syndrome was a squamous cell carcinoma of the vulva, described by Clark et al. in 1998. We observed a male patient with Job's syndrome diagnosed at age three who presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…Complications such as intracranial and coronary arterial aneurysms [5][6][7][8] and malignancy including lymphoma [9][10][11] have been reported previously. AD-HIES results from mutations in the Signal Transducer and Activator of Transcription 3 (STAT3) transcription factor, which leads to a loss of STAT3 function, poor Th17 cell differentiation, aberrant CD8+ T cell differentiation, and abnormal B cell function [12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 94%
“…Complications such as intracranial and coronary arterial aneurysms [5][6][7][8] and malignancy including lymphoma [9][10][11] have been reported previously. AD-HIES results from mutations in the Signal Transducer and Activator of Transcription 3 (STAT3) transcription factor, which leads to a loss of STAT3 function, poor Th17 cell differentiation, aberrant CD8+ T cell differentiation, and abnormal B cell function [12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 94%
“…Regarding the solid lung tumors , there are only few case reports in the literature ( leiomyoma, pulmonary adenocarcinoma ) and this respiratory complication is considered to be in general rare in PID patients (72, 73). Pulmonary comprise due to metastasis (origin from, e.g., gastric carcinoma) is more often seen than primary pulmonary malignancy (7).…”
Section: Respiratory Manifestations Of Primary Immunodeficienciesmentioning
confidence: 99%
“…Further studies have shown that patients with HIES do not seem to be at increased risk of other cancers. 21,22 …”
Section: Differential Diagnosismentioning
confidence: 99%